Challenges in Educating about Sustainability and Development Theory - Bharti, Poonam (JOURNAL OF INDIAN EDUCATION, 2020)
The idea that brought the world to rethink development emerged from limits to growth and offered humanity to give a different direction to development theory. This article proposes to examine and explore sustainability as a goal in the life of an individuals and to understand whether the growing consciousness among people results in some affirmative action by developing a critique of the key concept of sustainability and interconnectedness.